Penerapan Perencanaan dan Pengendalian Internal Dalam Pengelolaan Alokasi Dana Desa (Studi Pada Desa Jagamukti, Desa Citanglar dan Desa Buniwangi) - Maulidah, Resti Wahyuni (Jati: Jurnal Akuntansi Terapan Indonesia, 2020)
Implementation of Village Fund Allocation (ADD) Planning and Management in Jagamukti Village, Citanglar Village and Buniwangi Village Surade District Sukabumi District.This study aims to determine the implementation of planning and internal control in the management of Village Fund Allocation in Citanglar Village, Jagamukti Village and Buniwangi Village in 2018. This research method uses descriptive methodological data collection is done by interviewing techniques. This study took speakers from the village government, namely the Village Secretary and from Community Leaders. The results of this study showed that Citanglar Village, Jagamukti Village and Buniwangi Village had implemented internal planning and control in the management of Village Dans Allocation which were implemented well.